2021
DOI: 10.1111/bcp.15063
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting creatine phosphokinase elevation during daptomycin therapy using a combination of machine learning and conventional methods

Abstract: Aims: Musculoskeletal toxicity is a typical side effect of daptomycin (DAP). However, the risk factors have not been well established. Here, we aimed to identify independent factors affecting DAP-induced musculoskeletal toxicity using a combination of machine learning and conventional statistical methods.Methods: A population-based, retrospective, observational cohort study was conducted using the Japanese electronic medical record database. Patients who received DAP between October 2011 and December 2020 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
(229 reference statements)
2
9
0
Order By: Relevance
“…In studies examining the risk factors for CPK elevation during combined daptomycin and statin treatment, African American ethnicity was cited as a risk factor, similar to other findings that African Americans have a higher risk of CPK elevation during statin treatment [ 7 , 8 ]. Similar results were reported by Imai et al, who investigated Japanese patients [ 28 ]. In our study, 8 of the 17 patients with CPK elevation received statins concomitantly with daptomycin.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In studies examining the risk factors for CPK elevation during combined daptomycin and statin treatment, African American ethnicity was cited as a risk factor, similar to other findings that African Americans have a higher risk of CPK elevation during statin treatment [ 7 , 8 ]. Similar results were reported by Imai et al, who investigated Japanese patients [ 28 ]. In our study, 8 of the 17 patients with CPK elevation received statins concomitantly with daptomycin.…”
Section: Discussionsupporting
confidence: 90%
“…Concomitant statin use was described as a risk factor for daptomycin-associated CPK elevation in the package insert of daptomycin [ 9 ]. Case–control studies by Dare et al and Imai et al confirmed the relationship between daptomycin and CPK elevation based on the CPK levels of >ULN and >1000 IU/L or >2000 IU/L, respectively [ 6 , 28 ]. In several studies, statins were not associated with daptomycin-associated CPK elevation [ 7 , 8 , 25 , 27 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…We then excluded 87 articles, including studies that lacked data on concomitant statin use (74 articles), those without details on the number of patients taking statins (6 articles), studies without data on the number of patients with elevated CPK (4 articles), studies without patients with concomitant statins (two articles) and studies without data on the daptomycin group (one article). Finally, 9 studies were included in the metaanalysis to define CPK elevation as CPK levels ≥ULN, 20,26,27,[31][32][33][34][35][36] and 9 that defined CPK elevation as levels ≥5Â ULN. 6,10,20,21,28,[36][37][38][39] Two studies were included in the both analyses.…”
Section: Search Resultsmentioning
confidence: 99%
“…Finally, 9 studies were included in the metaanalysis to define CPK elevation as CPK levels ≥ULN, 20,26,27,[31][32][33][34][35][36] and 9 that defined CPK elevation as levels ≥5Â ULN. 6,10,20,21,28,[36][37][38][39] Two studies were included in the both analyses. 20,36…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation